Research progress on the role of immediate early genes in the pathogenesis of temporal lobe epilepsy - ZHANG Wei; QI Shuya; TAN Guohe (Guangxi Yike Daxue xuebao)
Temporal lobe epilepsy (TLE) is a common chronic neurological disorder caused by highly synchronized abnormal discharges of neurons in the cerebral cortex. Although most epileptic symptoms can be effectively controlled by antiepileptic drugs, about 30% of patients with TLE still develop resistance to the drugs, and then develop refractory epilepsy. Thus, it is particularly important to further explore the new mechanisms underlying the molecular pathogenesis of TLE. Coverging studies have indicated that immediate early genes (IEGs) play a vital role in limbic epileptogeneis. These genes participate in the limbic epileptogeneis by altering neuronal excitability/inhibitory balance, neuronal death, and synaptic reorganization. This paper presents a comprehensive review of the specific roles and molecular mechanisms of several classic IEGs in the pathogenesis of TLE, aiming to enhance the understanding of the pathogenesis of TLE and provide new insights into relevant clinical research.